Listening through houses: Changing communities of sounds in northern Laos - Rosalie Stolz (Anuac, 2021)
In the uplands of northern Laos, in which bamboo and timber houses prevailed, concrete houses are now on the rise. It will be argued that houses can be used as prisms to illuminate processes of social change. Drawing on experiences of staying in both a timber house and a new concrete one over the course of long-term ethnographic fieldwork among the Khmu, a key experiential difference will be analysed: their different soundscapes. While one can easily listen through the cracks and spaces between timber boards, concrete walls produce a perceivable barrier between inside and outside. It will be argued that the changing materiality of the house and its (sonic) repercussions contribute to shaping a different relationship between the house, its residents, and the village. Finally, it will be argued that when inquiring into the shifting sensory experience of living in concrete houses in a social context in which houses are of central importance yet are not the places where locals spend much of their time, emphasis should not solely be given to the house but to other meaningful locales of sociality.